DIABETES EDUCATOR STATUS AND WELL-BEING STUDY IN PAHANG - Sun, Jia Miin; Shahrizal, Shudim Saiful; See, Chee Keong (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Diabetes educators (DEs) are essential in shared decision-making for diabetes care. Psychological and social factors influence their well-being, motivation, and efficiency in delivering care. METHODOLOGY This is a cross-sectional study conducted from June to November 2024, involving DEs in Pahang using the QPS Nordic questionnaire. Responses were measured on a Likert scale (1: Very Seldom/Never to 5: Very Often/Always), assessing job demands, role clarity, role conflict, job predictability, mastery perception, leadership support, social climate, work-life balance, and motivation. RESULT Seventy-five DEs participated in the study (mean age: 39.3 years, SD: 5.5). Fifty-seven percent were hospital-based (80% in wards, 20% in clinics), and 43% worked in primary care. 65% had over five years of experience. The respondents had a neutral view of their quantitative job demands (Mean score: 3.09) and had good role clarity in their institution (Mean score: 3.96). However, they faced significant conflict in completing their responsibilities and inadequate resources in their daily work. Job predictability was perceived as neutral in both short-term and long-term aspects. Most respondents were positive about their work quality and were satisfied with their ability to complete tasks. The respondents viewed their immediate superiors positively, particularly in listening to their work-related problems. Despite this, the respondents had a neutral view on superiors’ empowering leadership or creating space to voice opinions. Respondents felt there was no job interference with their personal life (Mean score: 2.71). They were highly motivated to achieve success, recognition, and security in their careers, with a focus on a peaceful and healthy working environment. CONCLUSION Diabetes educators in this study demonstrated high motivation to excel in their profession but faced significant difficulties in fulfilling their roles. Emphasizing empowering leadership and fostering a supportive work environment are crucial to improving diabetes educators' motivation, learning, and efficiency.